A Leap-Frog Finite Difference Method for Strongly Coupled System from Sweat Transport in Porous Textile Media - Qian Zhang; Chao Huang (Journal of Mathematics)
In this paper, we present an uncoupled leap-frog finite difference method for the system of equations arising from sweat transport through porous textile media. Based on physical mechanisms, the sweat transport can be viewed as the multicomponent flow that coupled the heat and moisture transfer, such that the system is nonlinear and strongly coupled. The leap-frog method is proposed to solve this system, with the second order accuracy in both spatial and temporal directions. We prove the existence and uniqueness of the solution to the system with optimal error estimates in the discrete L2 norm. Numerical simulations are presented and analyzed, respectively.